On the monophyly of subfamily Tectarioideae (Polypodiaceae) and the phylogenetic placement of some associated fern genera - Wang, Fa-Guo; Barratt, Sam; Falcón, Wilfredo; Fay, Michael F.; Lehtonen, Samuli; Tuomisto, Hanna; Xing, Fu-Wu; Christenhusz, Maarten J. M. (Phytotaxa, 2014)
The fern genus Tectaria has generally been placed in the family Tectariaceae or in subfamily Tectarioideae (placed in Dennstaedtiaceae, Dryopteridaceae or Polypodiaceae), both of which have been variously circumscribed in the past. Here we study for the first time the phylogenetic relationships of the associated genera Hypoderris (endemic to the Caribbean), Cionidium (endemic to New Caledonia) and Pseudotectaria (endemic to Madagascar and Comoros) using DNA sequence data. Based on a broad sampling of 72 species of eupolypods I (= Polypodiaceae sensu lato) and three plastid DNA regions (atpA, rbcL and the trnL-F intergenic spacer) we were able to place the three previously unsampled genera. Our results show that Cionidium, like Ctenitopsis, Fadyenia, Hemigramma and Quercifilix, is embedded in Tectaria, and the monophyly of Tectaria is therefore corroborated only if these segregate genera are included. Hypoderris is sister to Tectaria brauniana and together they are sister to Triplophyllum, which was found to be monophyletic. Despite their morphological similarity with Tectaria, the genera Pleocnemia and Pseudotectaria were placed in Dryopteridoideae. Polypodiaceae subfamily Tectarioideae (former family Tectariaceae) is hereby defined to include Arthropteris, Hypoderris, Pteridrys, Tectaria and Triplophyllum. Aenigmopteris may also belong here, but this genus remains unsampled.